Genome wide characterization and expression analysis of CrRLK1L gene family in wheat unravels their roles in development and stress-specific responses - Gawande, Nilesh D.; Sankaranarayanan, Subramanian (Frontiers in Plant Science, 2024)
Catharanthus roseus receptor-like kinase 1-like (CrRLK1L) genes encode a subfamily of receptor-like kinases (RLK) that regulate diverse processes during plant growth, development, and stress responses. The first CrRLK1L was identified from the Catharanthus roseus, Madagascar periwinkle, commonly known as Madagascar periwinkle. Subsequently, CrRLK1L gene families have been characterized in many plants. The genome of T. aestivum encodes 15 CrRLK1L genes with 43 paralogous copies , with three homeologs each, except for -2-D and -7-A, which are absent. Chromosomal localization analysis revealed a markedly uneven distribution of CrRLK1L genes across seven different chromosomes, with chromosome 4 housing the highest number of genes, while chromosome 6 lacked any CrRLK1L genes. Tissue-specific gene expression analysis revealed distinct expression patterns among the gene family members, with certain members exhibiting increased expression in reproductive tissues.Gene expression analysis in response to various abiotic and biotic stress conditions unveiled differential regulation of gene family members. Cold stress induces CrRLK1Ls -4-B and -15-A while downregulating -3-A and -7B. Drought stress upregulates -9D, contrasting with the downregulation of -7D. In response to heat stress, CrRLK1Ls-15-B and -15-D were highly induced in response to 1hr of drought and combined drought and heat stress, whereas -10-B is downregulated. Similarly, in response to NaCl stress, only CrRLK1L homeologs were induced.Fusarium graminearum and Claviceps purpurea inoculation induces homeologs of CrRLK1L-6 and -7. The analysis of cis-acting elements in the promoter regions identified specific elements crucial for plant growth and developmental processes. This comprehensive genome wide analysis and expression study providegenome-wide analysis and expression study providess valuable insights into the essential functions of CrRLK1L members in wheat.